Pelindungan Rezim Hukum Hak Asasi Manusia (HAM) dan Hukum Humaniter Internasional (HHI) Bagi Angkatan Bersenjata; Sebuah Perspektif - Arief Fahmi Lubis (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2021)
On the one side, there is the authority to use armed force, but on the other side, there is an obligation to protect objects by the regime of Human Rights Law and International Humanitarian Law which has created a need for certainty of restrictions. In the Human Rights Law regime, the use of force is limited to a situation which is an absolute necessity. The purpose of this research is to know that the first protection aspect of Human Rights Law and International Humanitarian Law is in the context of providing a legal framework to move according to their needs. This research was conducted using a normative juridical research method by conducting a comprehensive study based on laws and regulations as well as empirical juridical research, namely conducting a study based on observations of the handling of national security and defence threats in Indonesia involving the TNI. The conclusion of this research is that International Humanitarian Law, especially in International Armed Conflict (